2011
DOI: 10.1375/bech.28.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Developing and PilotingePACT: A Flexible Psychological Treatment for Depression in People Living With Chronic Spinal Cord Injury

Abstract: Accessibility, stigma and adverse effects of self-reliance can hinder the receipt of psychological treatments, especially in people living with chronic illness or disability. The aim of this study was to develop and pilot a flexible online psychological treatment using CBT and positive-psychology based techniques, for individuals with spinal cord injury (SCI) who also lived with depression or both depression and anxiety. A multiple case study approach provided in-principle evidence of the acceptability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…First, one-group pre-test/post-test design was used to evaluate the effectiveness of the intervention program. However, the use of this methodological approach is not uncommon in the literature, particularly for preliminary evaluation of positive psychology intervention programs at the initial stage of development (Bonhote et al, 1999;Carson et al, 2010;Lantz, Buchalter, & McBee, 1997;Migliorini, Tonge, & Sinclair, 2011). Future research should adopt RCT for assessing the outcomes of this intervention in order to minimize potential confounding effects.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…First, one-group pre-test/post-test design was used to evaluate the effectiveness of the intervention program. However, the use of this methodological approach is not uncommon in the literature, particularly for preliminary evaluation of positive psychology intervention programs at the initial stage of development (Bonhote et al, 1999;Carson et al, 2010;Lantz, Buchalter, & McBee, 1997;Migliorini, Tonge, & Sinclair, 2011). Future research should adopt RCT for assessing the outcomes of this intervention in order to minimize potential confounding effects.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Preliminary findings using IT to support the health and well-being after SCI have been promising. For instance, using IT to deliver online psychological treatment can lead to improvements in symptoms of depression and anxiety following SCI [14]. Additional work has shown improvements in psychosocial adjustment [15][16][17][18], quality of life (QoL) [19], and physical symptoms [17,18] following counseling delivered via telephone or videoconference (see Dorstyn et al 2013 for review [20]).…”
Section: Introductionmentioning
confidence: 99%
“…7,8,12 Still, the amount of participants not completing one module was considerable in this study, despite the intensive telephone support. Different factors may influence adherence to this type of treatment, such as disease severity 13 and the ability to reflect on one's thoughts and feelings that such programmes require.…”
Section: Feasibilitymentioning
confidence: 81%
“…Migliorini et al 7 also found improvement of mood after completion of their intervention, and this effect was neither universal nor significant. So far, the results of online positive psychological interventions do not compare positively with the results of traditional or telephone-based cognitive behavioural therapy of depression in persons with SCI.…”
Section: Satisfactionmentioning
confidence: 94%
See 1 more Smart Citation